2015
DOI: 10.1111/ajt.13235
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Tuberculosis After Liver Transplantation in an Endemic Area: A Nationwide Population-Based Matched Cohort Study

Abstract: These authors contributed equally to this work.Morbidity and mortality from tuberculosis (TB) are high in Taiwan. We conducted a nationwide populationbased matched cohort study using data retrieved from the Taiwan's National Health Insurance Research Database to determine the impact of TB after liver transplantation (LT). During 2000-2011, we identified 3202 liver transplant recipients and selected subjects from the general population matched for age, sex, and comorbidities on the same index date of recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
(43 reference statements)
3
30
0
Order By: Relevance
“…A total of 253 TB cases among liver recipients were reported in 20 cohort studies and 22 case reports . Of these, 78 of 106 cases (73.58%) were male.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 253 TB cases among liver recipients were reported in 20 cohort studies and 22 case reports . Of these, 78 of 106 cases (73.58%) were male.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 253 TB cases among liver recipients were reported in 20 cohort studies 141,142,144,146,147,149,151,153,157,161,163,169,171,172,175,177,184,185,187,189 and 22 case reports. 8,10,15,18,22,27,31,32,39,45,47-49, 72,76,77,93,104,114,115,124,137 Of these, 78 of 106 cases (73.58%) were male.…”
Section: Liver Transplant Recipientsmentioning
confidence: 99%
“…Specifically, we found an article in which a kidney transplant recipient undergoing treatment with everolimus suffered from TB . In addition to that study, an association was found between the use of mTOR inhibitors (sirolimus and everolimus) and the development of TB after transplantation in a cohort of liver transplant recipients in Taiwan . As regards the pathophysiological mechanism that could favor the development of TB because of everolimus therapy, it is known that everolimus inhibits cellular immunity and possibly stimulates the production of interleukin‐10, which may facilitate the reactivation of latent infections.…”
Section: Discussionmentioning
confidence: 96%
“…The cumulative risk of tuberculosis in liver transplantation is estimated to be 0.8 percent in developed countries and 2 percent in developing countries . The disease is associated with significant morbidity and mortality in developed and developing countries . The risk varies depending on transplanted organ and tuberculosis epidemiology in the donor/recipient population.…”
Section: Introductionmentioning
confidence: 99%